Influence of music on the level of physical fitness of the students practicing rugby (rugby players students) - Zh.L. Kozina; V.E. Kalinicenko; M. Cretu; A.V. Osiptsov; M.D. Kudryavtsev; S.B. Polishchuk; A.S. Ilnickaya; A.O. Minenok (Physical Education of Students, 2018)
Purpose: to develop a training technology with the application of music at rugby training of 16-17-year-olds players.